Effect of microwave and conventional heating on structural, functional and antioxidant properties of bovine serum albumin-maltodextrin conjugates through Maillard reaction. (October 2017) - Nasrollahzadeh, Farzaneh; Varidi, Mehdi; Koocheki, Arash; Hadizadeh, Farzin
Abstract: In present study, effect of conventional heating (CH) and microwave heating (MH) on Maillard reaction (MR) progression and structural, functional and antioxidant properties of glycated protein was investigated. The glycation process was carried out at 90 °C, in bovine serum albumin–maltodextrin system. The extent of glycation was assessed by ortho -phthaldialdehyde and absorbance at 420 nm. Afterwards, K - means clustering was applied to classify all treatments into three levels of glycation (low, medium, high). Subsequently, SDS-PAGE, structural (surface hydrophobicity and circular dichroism), functional and antioxidant (DPPH radical scavenging) properties were measured within chosen treatments. Results showed that MH was more effective on the reduction of free amino groups and increase in absorbance at 420 nm more than CH ( p <0.05). On the other hand, higher values in solubility, emulsion activity and foam capacity were obtained during MH heating which could be attributed to different structural changes of proteins under MH and CH. Graphical abstract: Highlights: The effect of conventional and microwave heating on Maillard reaction was investigated. Maillard reaction progression under microwave was faster than conventional heating. Conformational changes of BSA were different under microwave and conventional heating. Functional properties were improved due to microwave heating. Microwave increased DPPH radical scavenging in comparison to conventional heating.